Collective Leadership in the Structure of Legislative (Representative) State Power Bodies of the Russian Federation Subjects in the Siberian Federal District - Bykova A. G. (Vestnik Omskoj Ûridičeskoj Akademii, 2014)
The article deals with the structure, composition, formation procedure, powers of the collegial leadership of the legislative (representative) state power agencies of the Russian Federation subjects in the Siberian Federal District